100 Global longitudinal strain by CMR improves prognostic stratification in acute myocarditis presenting with normal LVEF. (8th December 2021) - Porcari, Aldostefano; Merlo, Marco; Baggio, Chiara; Gagno, Giulia; Cittar, Marco; Barbati, Giulia; Paldino, Alessia; Castrichini, Matteo; Vitrella, Giancarlo; Pagnan, Lorenzo; Cannata, Antonio; Andreis, Alessandro; et al.
Abstract: Aims: Prognostic stratification of acute myocarditis (AM) presenting with normal left ventricular (LV) ejection fraction (EF) relies mostly on late gadolinium enhancement (LGE) at cardiac magnetic resonance (CMR) imaging. In this specific AM population, LV peak global longitudinal strain (LV-GLS) measured by feature tracking (FT) analysis might provide further prognostic information. Methods and results: Data of patients undergoing CMR for clinically suspected AM in seven European Centres, between January 2013 and August 2020, were retrospectively analysed. Those patients fulfilling CMR Lake Louise Criteria (LLC) for the diagnosis of AM and presenting with normal LVEF (≥50%) were included. Patients presenting with heart failure (HF) or significant arrhythmic events, LVEF <50% or haemodynamic instability were excluded. CMR-LGE extent (localized vs. diffuse), localization (subepicardial vs. mid-wall), and distribution (anteroseptal vs. inferolateral) were visually assessed. LV-GLS was measured by dedicated software. The primary outcome was the first occurrence of an adverse cardiovascular event (ACE) including a composite of cardiac death, development of heart failure, life-threatening arrhythmias, or development of LVEF <50%. In patients experiencing more than one event, the first one was considered for the outcome analysis. Of 389 patients with clinically suspected AM, 256 (66%) had confirmed AM with LVEF ≥50% and were included. Median age was 36 years, 71% were males, median LVEF was 60%, and median LV-GLS −17.3%. CMR was performed at a median time of 4 (IQR: 2–12) days from hospital admission. At a median follow-up of 27 months, 24 (9%) patients experienced at least one ACE with development of LVEF <50% accounting for 17 [71%]. Compared to the others, patients experiencing ACEs had lower median LV-GLS values at baseline (−13.9% vs. −17.5%, P = 0.001). At Kaplan–Meier analysis, impaired LV-GLS (both considered as >-20% or quartiles), diffuse and mid-wall LGE were associated with a significantly higher rate of ACEs. LV-GLS remained independently associated with ACEs after adjustment for diffuse or mid-wall LGE as covariate at bivariable analysis. Conclusions: In AM with LVEF ≥50%, LV-GLS provides independent prognostic value over LGE, improving risk stratification and providing a rationale for further studies of therapy in this cohort. 100 Figure